2015
DOI: 10.1002/uog.14762
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of first‐ and second‐trimester uterine artery pulsatility index measured by transvaginal and transabdominal ultrasound

Abstract: Objectives To examine and compare the reproducibility of measurement of first-and second-trimester uterine artery pulsatility index (UtA-PI) using transabdominal (TAS) and transvaginal (TVS) ultrasound. Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 32 publications
4
25
1
Order By: Relevance
“…Adherence to a standardized methodology is essential to ensure reproducible measurements. Studies evaluating the reproducibility of this technique have shown interobserver intraclass/concordance correlation coefficients of 0.80–0.85. However, limits of agreement were found be as high as ± 35% for the transvaginal and ± 40% for the transabdominal approach.…”
Section: Screening For Pre‐eclampsia Using Ultrasoundmentioning
confidence: 99%
“…Adherence to a standardized methodology is essential to ensure reproducible measurements. Studies evaluating the reproducibility of this technique have shown interobserver intraclass/concordance correlation coefficients of 0.80–0.85. However, limits of agreement were found be as high as ± 35% for the transvaginal and ± 40% for the transabdominal approach.…”
Section: Screening For Pre‐eclampsia Using Ultrasoundmentioning
confidence: 99%
“…Intra-and interobserver reproducibility tests were not performed because all ultrasound examinations were carried out only two examiners with full registration by the FMF. In a recent study assessing the intra-and interobserver reproducibility of transabdominal and transvaginal ultrasound in first and second trimesters, both techniques have demonstrated similar reproducibility in the assessing of UtA Doppler PI (8). In addition, when the mean UtA PI Doppler values was measured by transvaginal ultrasound at 20-24w6d of gestation, decrease in UtA Doppler PI values with advancing GA was observed.…”
Section: Discussionmentioning
confidence: 91%
“…Specifically, transvaginal approach was used at 11-14 weeks of gestation, whereas transabdominal approach was used at 15-41 weeks. Ferreira et al (8) compared the reproducibility of UtA Doppler PI in the first and second trimesters of pregnancy using both transvaginal and transabdominal scan and observed that PI was evenly significantly higher in both trimesters using transvaginal approach.…”
Section: Introductionmentioning
confidence: 99%
“…Although the clinician may be prone to take for granted that Doppler measurements are reliable, unfortunately, they are subject to a great variation. Doppler acquisitions have been shown to be poorly reproducible, and this is true not only for fetal Doppler but also for UtA measurement during the first and second trimester …”
Section: Discussionmentioning
confidence: 99%